Unlocking Green Potential: How the EGSS Sector Can Reduce NEET Rates in the EU - Spasov, Lyudmil; Raychev, Stefan (Research Papers, 2025)
This article establishes the significant relationship between the growth of the Environmental Goods and Services Sector (EGSS) and the reduction of NEET (Not in Education, Employment, or Training) rates across 33 European countries from 2013 to 2022. Through robust data analysis, the findings reveal an inverse correlation between EGSS expansion and NEET rates, underscoring the sector’s potential to drive youth engagement in the green economy. The results suggest that targeted educational and training programs aligned with green sector demands could play a critical role in fostering socio-economic stability and reducing youth disengagement.